Co-digestion of manure and industrial waste – The effects of trace element addition. (January 2016) - Nordell, Erik; Nilsson, Britt; Nilsson Påledal, Sören; Karisalmi, Kaisa; Moestedt, Jan
Highlights: Addition of iron and trace elements improved the biogas process. At high organic loadings biogas production increased with 10%. The biogas production rate increased with 24%, suggesting higher microbial activity. Volatile fatty acid accumulated in absence of trace element addition. Methane emissions was 49% lower in the digestate from reactor with trace elements. Abstract: Manure is one of the most common substrates for biogas production. Manure from dairy- and swine animals are often considered to stabilize the biogas process by contributing nutrients and trace elements needed for the biogas process. In this study two lab-scale reactors were used to evaluate the effects of trace element addition during co-digestion of manure from swine- and dairy animals with industrial waste. The substrate used contained high background concentrations of both cobalt and nickel, which are considered to be the most important trace elements. In the reactor receiving additional trace elements, the volatile fatty acids (VFA) concentration was 89% lower than in the control reactor. The lower VFA concentration contributed to a more digested digestate, and thus lower methane emissions in the subsequent storage. Also, the biogas production rate increased with 24% and the biogas production yield with 10%, both as a result of the additional trace elements at high organic loading rates. All in all, even though 50% of the feedstock consisted of manure, trace element addition resulted in multiple positive effects and a more reliable process with stable and high yield.